Cross-adaptation between heat and hypoxia: mechanistic insights into aerobic exercise performance - Sotiridis, A.; Debevec, T.; Geladas, N.; Mekjavic, I. B. (American Journal of Physiology - Regulatory, Integrative and Comparative Physiology, 2022)
Acclima(tiza)tion to heat or hypoxia enhances work capacity in hot and hypoxic environmental conditions, respectively; an acclimation response is considered to be mediated by stimuli-specific molecular/systemic adaptations and potentially facilitated by the addition of exercise sessions. Promising findings at the cellular level provided the impetus for recent studies investigating whether acclimation to one stressor will ultimately facilitate whole body performance when exercise is undertaken in a different environmental condition. The present critical Mini-Review examines the theory of cross-adaptation between heat and hypoxia with particular reference to the determinants of aerobic performance. Indeed, early functional adaptations (improved exercise economy and enhanced oxyhemoglobin saturation) succeeded by later morphological adaptations (increased hemoglobin mass) might aid acclimatized humans perform aerobic work in an alternative environmental setting. Longer-term acclimation protocols that focus on the specific adaptation kinetics (and further allow for the adaptation reversal) will elucidate the exact physiological mechanisms that might mediate gains in aerobic performance or explain the lack thereof.